RISK-LADEN WORKING LIVES OF CHILD PROTECTION SOCIAL WORKERS IN SOUTH AFRICA - Truter, Elmien; Fouche, Ansie (Social Work/Maatskaplike Werk, 2019)
<span style="font-family: 'Times New Roman','serif'; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 'MS Mincho'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">This study reports on the findings of semi-structured interviews with ten social workers<span style="font-family: 'Times New Roman','serif'; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 'MS Mincho'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">employed by designated child protection organisations in Gauteng, South Africa to explore their lived experiences of workplace risks and subsequent negative outcomes. Thematic analysis of transcribed interviews yielded risk factors embedded in the socio-ecological model, namely <span style="font-family: 'Times New Roman','serif'; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">intrapersonal (personality traits and the dichotomy of human vs. professionalism); interpersonal (unsupportive supervisors; lack of co-operation among professionals); institutional (challenges unique to child protection social work); community (unrealistic expectations from communities); societal / public policy (lack of funding and resources, political interference)<span style="font-family: 'Times New Roman','serif'; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 'MS Mincho'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">. A discussion follows and the way forward is deliberated